1990
DOI: 10.1161/01.hyp.15.6.779
|View full text |Cite
|
Sign up to set email alerts
|

Microvessel changes in hypertension measured by Griffonia simplicifolia I lectin.

Abstract: Commonly used methods for assessing reductions in microvascular density (rarefaction) in hypertension detect only perfused microvessels. In the present study, samples of cremaster and spinotrapezius muscles were taken from rats with chronic (4-week) reduced renal mass hypertension and normotensive sham-operated control rats, as well as from 12-week-old spontaneously hypertensive rats and their normotensive Wistar-Kyoto control strain. Mean arterial pressure was 149±8 mm Hg in the rats with reduced renal mass h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 14 publications
4
59
0
1
Order By: Relevance
“…In comparison to tissues harvested from WKY rats, SHR mesenteric tissues contain smaller microvascular networks, consistent with previously documented microvascular rarefaction in other organs of the SHR (Chen et al, 1981;Greene et al, 1990;Hutchins and Darnell, 1974;Kobayashi et al, 2005;Prewitt et al, 1982). 15/15 SHR isolated networks from 6 tissues were classified as small defined by being contained to a 10× field of view.…”
Section: Resultssupporting
confidence: 84%
“…In comparison to tissues harvested from WKY rats, SHR mesenteric tissues contain smaller microvascular networks, consistent with previously documented microvascular rarefaction in other organs of the SHR (Chen et al, 1981;Greene et al, 1990;Hutchins and Darnell, 1974;Kobayashi et al, 2005;Prewitt et al, 1982). 15/15 SHR isolated networks from 6 tissues were classified as small defined by being contained to a 10× field of view.…”
Section: Resultssupporting
confidence: 84%
“…10 Other studies with a longer duration have shown similar findings. 9,19,27 It is possible that salt, rather than working through BP, may have a direct effect on microvascular network and could be one of the underlying causes for the microvascular rarefaction that occurs in hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining TA was lightly fixed overnight in 0.25% formalin solution and sectioned longitudinally. TA sections were stained with lectin, and vessel density was determined as previously described (21,38).…”
Section: Experimental Protocol the Medical College Of Wisconsin (Mcw)mentioning
confidence: 99%